2014
DOI: 10.3389/fnagi.2014.00254
|View full text |Cite
|
Sign up to set email alerts
|

Homotaurine Induces Measurable Changes of Short Latency Afferent Inhibition in a Group of Mild Cognitive Impairment Individuals

Abstract: Current treatment options for patients with Alzheimer’s disease (AD) are limited at providing symptomatic relief, with no effects on the underlying pathophysiology. Recently, advances in the understanding of the AD pathogenesis highlighted the role of ABeta (Aβ) oligomers particularly interfering with mechanisms of cortical plasticity such as long-term potentiation (LTP) and long-term depression (LTD). These findings led to the development of potential anti-amyloid therapies, and among them homotaurine, a glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…We also report that PD patients in treatment with homotaurine significantly improved in UPDRS-I score and Epworth Scale score at the end of the study, while no differences in any of the assessment scales scores was revealed in the PD controls group. Moreover, patients in both groups showed no changes of performance in any neuropsychological test, and this is in line with previous studies, which failed to demonstrate an effect of homotaurine treatment on cognitive functions as measured by means of battery of neuropsychological tests in AD patients [5,29]. In detail, in the Alphase study, authors did not find significant change over 78 weeks in the neuropsychological variables (Alzheimer's Disease Assessment Scale-Cognitive Subscale and Clinical Dementia Rating-Sum of boxes), but they showed a trend toward greater decrease in volumetric MRI of the hippocampus [29].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also report that PD patients in treatment with homotaurine significantly improved in UPDRS-I score and Epworth Scale score at the end of the study, while no differences in any of the assessment scales scores was revealed in the PD controls group. Moreover, patients in both groups showed no changes of performance in any neuropsychological test, and this is in line with previous studies, which failed to demonstrate an effect of homotaurine treatment on cognitive functions as measured by means of battery of neuropsychological tests in AD patients [5,29]. In detail, in the Alphase study, authors did not find significant change over 78 weeks in the neuropsychological variables (Alzheimer's Disease Assessment Scale-Cognitive Subscale and Clinical Dementia Rating-Sum of boxes), but they showed a trend toward greater decrease in volumetric MRI of the hippocampus [29].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, patients in both groups showed no changes of performance in any neuropsychological test, and this is in line with previous studies, which failed to demonstrate an effect of homotaurine treatment on cognitive functions as measured by means of battery of neuropsychological tests in AD patients [5,29]. In detail, in the Alphase study, authors did not find significant change over 78 weeks in the neuropsychological variables (Alzheimer's Disease Assessment Scale-Cognitive Subscale and Clinical Dementia Rating-Sum of boxes), but they showed a trend toward greater decrease in volumetric MRI of the hippocampus [29]. Authors suggested that changes in cognitive and neurobiological measures might not occur over the same time period and they might be considered as 25 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Homotaurine (3-aminopropanesulfonate), an analogue of 4-aminobutyrate (γ-aminobutyric acid, GABA), is a small natural aminosulfonate compound identified in different species of marine red algae (Acrosorium uncinatum, Cladophora densa, Chondrus ocellatus, Gratelupia livida and Rhodymenia palmataa) and then chemically synthesized under the name of tramiprosate [10]. This substance may interfere with several cellular pathways and exert neuroprotective and neurotropic activities through different mechanisms including effects against the oxidative damage to DNA, antifibrillogenic activity, and antinociceptive and analgesic activities, related to the activation of GABA type-A receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic effects of taurine remain to be investigated in demented animal models with AD pathology. Considering the reevaluation of anti-amyloidogenic homotaurine for the potential role to ameliorate the cholinergic transmission in early AD, its analog compounds such as taurine are valuable therapeutic candidates for both cognitive enhancement and disease-modification (Figure 1) 27 . In this study, we examined both symptomatic and diseasemodifying effects of taurine in the demented adult APP/PS1 transgenic AD mouse model.…”
mentioning
confidence: 99%